Discrete mathematical structures - Kolman, Bernanrd; Busby, Robert C. ;Ross, Sharon Cutler (New York, NY : Pearson, 2018)
Discrete Mathematical Structures, 6th Edition, offers a clear and concise presentation of the fundamental concepts of discrete mathematics. Ideal for a one-semester introductory course, this text contains more genuine computer science applications than any other text in the field. This book is written at an appropriate level for a wide variety of majors and non-majors, and assumes a college algebra course as a prerequisite.
1. Fundamentals 2. Logic 3. Counting 4. Relations and Digraphs 5. Functions 6. Order Relations and Structures 7. Trees 8. Topics in Graph Theory 9. Semigroups and Groups 10. Languages and Finite-State Machines 11. Groups and Coding
Includes index.
Keywords: COMPUTER SCIENCE -- MATHEMATICS